2013
DOI: 10.1128/jvi.02864-12
|View full text |Cite
|
Sign up to set email alerts
|

Airway Delivery of an Adenovirus-Based Ebola Virus Vaccine Bypasses Existing Immunity to Homologous Adenovirus in Nonhuman Primates

Abstract: b Anti-adenovirus serotype 5 antibodies are capable of neutralizing adenovirus serotype 5-based vaccines. In mice and guinea pigs, intranasal delivery of adenovirus serotype 5-based vaccine bypasses induced adenovirus serotype 5 preexisting immunity, resulting in protection against species-adapted Ebola virus challenge. In this study, nonhuman primates were vaccinated with adenovirus serotype 5-based vaccine either intramuscularly or via the airway route (intranasally/intratracheally) in the presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…In these studies, Ad-IFN was administered through a single intramuscular injection per regimen to conveniently ensure full delivery of the formulation in an animal species that cannot inhale on demand. However, Ad-IFN is intended for delivery in the airway from a nasal spray, a delivery route that was recently shown to overcome existing immunity to homologous adenovirus in rodents and NHPs (19,20). Surviving animals across the different groups exhibited robust EBOVspecific B and T cell responses after challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, Ad-IFN was administered through a single intramuscular injection per regimen to conveniently ensure full delivery of the formulation in an animal species that cannot inhale on demand. However, Ad-IFN is intended for delivery in the airway from a nasal spray, a delivery route that was recently shown to overcome existing immunity to homologous adenovirus in rodents and NHPs (19,20). Surviving animals across the different groups exhibited robust EBOVspecific B and T cell responses after challenge.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the Ad5-PAopt-and rPA-immunized rats produced different subtypes of antibodies or that the cellular immune response in the Ad5-PAopt-immunized rats contributed to the protection. Studies from our group and others have demonstrated that intranasal vaccination with Ad5-based vaccines can bypass PEI (27,29). There, we observed that compared to intranasal immunization, even in the presence of intranasal anti-Ad5 PEI, the intramuscular injection induced effective immune responses to protect rats from anthrax LT challenge in a relatively short time.…”
Section: Discussionmentioning
confidence: 54%
“…Intranasal vaccination was observed as an effective vaccine delivery route in the presence of systemic or even mucosal pre-existing immunity to the Ad5 vector in guinea pigs [95], and use of hydrogel was found to be safe and effective as a delivery system for nasal immunization [96]. Of note, airway vaccination with an Ad5-based EBOV vaccine could efficiently bypass pre-existing immunity to Ad5 and induce protective immune responses in NHPs [97,98]. Altogether, the available data have shown great potential for adenovirus-based vaccines to be licensed in the future.…”
Section: Adenovirus-based Vaccinesmentioning
confidence: 99%